MANAJEMEN STRATEGI TRANSPORTASI LAUT DI TENGAH MASA PANDEMI MANAGEMENT STRATEGY OF MARINE TRANSPORTATION IN THE MIDDLE OF THE PANDEMIC - Budi Sitorus; Christina Natalia Sitorus (JURNAL JALASENA, 2021)
MANAJEMEN STRATEGI TRANSPORTASI LAUT DI TENGAH MASA PANDEMI MANAGEMENT STRATEGY OF MARINE TRANSPORTATION IN THE MIDDLE OF THE PANDEMIC Di tengah masa pandemi covid 19, berdampak pada sektor transportasi laut yang mengalami kenaikan jumlah penumpang angkutan laut dalam negeri selama Januari hingga Maret 2020 mencapai 6,1 juta orang atau naik 20,05% dibandingkan periode yang sama tahun 2019. Adapun jumlah barang yang diangkut selama Januari–Juni 2020 mencapai 143,9 juta ton atau naik 0,65% dibanding periode yang sama tahun 2019. Metodologi yang digunakan yaitu teknik pengumpulan data sekunder melalui studi pustaka, literatur. Analisis menggunakan analisis kebijakan dan analisis deskriptif. Hasil penelitian yaitu semakin meningkatnya animo masyarakat yang menggunakan transportasi di tengah pandemi melalui penerapan protokol kesehatan yang ketat, kinerja pelayanan transportasi laut seperti on time performance di atas 95%. In the midst of the pandemic covid 19, the impact on the marine transport sector which is experiencing a rise in the number of passenger sea transport in the country during the January to March 2020 reached 6.1 million people, up 20,05% compared to the same period in 2019. As for the amount of goods transported during January–June 2020 achieve 143,9 million tons, up 0.65% compared to the same period in 2019. The methodology used is secondary data collection techniques through the study of literature, the literature. The analysis of the use of policy analysis and descriptive analysis. The results of the research, namely the increasing interest of the public transportation in the middle of a pandemic through the implementation of the protocol strict health, performance services sea transport such as on-time performance above 95%.